Semelhança de triângulos e geometria dinâmica o trabalho em grupo na aprendizagem de conceitos - Santos, Marcelo Tadeu dos (2013)
This research describes a qualitative research. The theme is based on model theory of geometric thought the couple's van Hiele and assumptions relating to the use of technology-mediated instructional strategies for learning geometry. The proposal aims to enable students of the ninth year of elementary school reinforce preconceptions and build new concepts on the topic similarity of triangles. For this, we used the dynamic geometry software GeoGebra. The study included the following steps: the first was the definition of a group of studies and discussions, by lottery among the student volunteers searched the series, the second step was the presentation of tokens students exercise on the theme of Likeness triangles whose solution involved only the use of manipulatives (ruler, compass, etc.). Finally, it was proposed to solve the same exercises using the set of concepts, and previous acquired through the application of the same dynamic geometry software GeoGebra. The study to suggest that the intervention of dynamic geometry can help students overcome various problems encountered and understanding and appropriation of concepts and autonomy to tread their own paths may be favored by the proposal of group work